Efficacy and safety of acupuncture combined with Chinese Herbal Medicine for diabetic nephropathy: A protocol for systematic review and meta-analysis. Issue 35 (3rd September 2021) - Yu, Ziyang; Zhang, Wenfeng; Li, Borui; Bao, Pengjie; Wang, Fengyang; Sun, Jian; Song, Guojiao; Yin, Lu; Nan, Zheng
Abstract: Background: Diabetic nephropathy (DN) is one of the most serious complications in the development of diabetes mellitus, which has become the main cause of end-stage renal disease and one of the main causes of death in diabetic patients. With the prevalence of diabetes, the number of patients at risk for developing DN is increasing, with 20–40 percent of all patients with diabetes at risk for developing DN. Acupuncture and Chinese herbal medicine treatments are often combined to treat DN; however, there has been no meta-analysis on their synergistic effects. Therefore, we aimed to perform a systematic review and meta-analysis to estimate the effectiveness of acupuncture combined with Chinese herbal medicine for DN treatment. Methods: Nine electronic databases were retrieved for this study. The English databases mainly retrieved PubMed, Web of Science, Embase, AMED, and the Cochrane Library, while the CNKI, VIP, CBM, and Wanfang databases were used to retrieve the Chinese literature. There is no definite time limit for the retrieval literature, and the languages are limited to Chinese and English. We will consider articles published between database initiation and August 2021. We used Review Manager 5.4, provided by the Cochrane Collaborative Network for statistical analysis. Clinical randomized controlled trials related to acupuncture combined with Chinese herbal medicine for DN were included in this study. Research selection, data extraction, and research quality assessments were independently completed by two researchers. We then assessed the quality and risk of the included studies and observed the outcome measures. Results: This study provides a high-quality synthesis to assess the effectiveness and safety of acupuncture combined with Chinese herbal medicine for treating DN. Conclusion: This systematic review will provide evidence to determine whether acupuncture combined with Chinese herbal medicine is an effective and safe intervention for patients with DN. Ethics and dissemination: The protocol of the systematic review does not require ethical approval because it does not involve humans. This article will be published in peer-reviewed journals and presented at relevant conferences. Registration number: INPLASY202180018